PERSEPSI SISWA KELAS XII TERHADAP MAHASISWA PPL PRODI PENDIDIKAN SEJARAH DALAM PROSES PEMBELAJARAN DI SMA N 3 KOTA JAMBI - Wulandari, Fitri; ZE, Deki Syaputra (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
In the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers, it is stated that teachers are required to have four competencies, namely pedagogic competence, personality, social and professional competence obtained through professional education. PPL is a special practice for students which includes teaching practice, administration, guidance and counseling competencies as well as co-curricular or extra-curricular activities that apply at school. The purpose of this study was to determine the perception of Class XII Students towards PPL Students of History Education Study Program in the Learning Process at SMA N 3 Jambi City. The type of research applied is descriptive quantitative. The results of the research on the perception of class XII students of SMA Negeri 3 Jambi City towards PPL students of the Unbari History Education Study Program which consists of four competencies, namely pedagogic competence, personality competence, professional competence, and social competence. In the pedagogic competence the percentage of students' perceptions is 72.82% in the "Enough" category, in the personality competence the percentage of students' perceptions is 73.60% in the "Enough" category, in the social competence the percentage of students' perceptions is 70.29% in the "Enough" category, and professional the percentage of students' perceptions of 58.29% in the "Very Not Good" category. So overall regarding students' perceptions of PPL students of the History Education Study Program, it is in the "Enough" category with an average percentage of 69.42%.